Răspunsuri

2014-06-09T18:16:16+03:00
 \sqrt{7-4 \sqrt{3} }  =  \sqrt{4 -4 \sqrt{3} + 3 } (l-am scris pe 7 ca 4+3)

 \sqrt{4 -4 \sqrt{3} + 3 } = \sqrt{4 -4 \sqrt{3} + \sqrt{3}^2  }\\
=\sqrt{(2- \sqrt{3})^2} = 2- \sqrt{3} 

(l-am scris pe ca \sqrt{3}^2 şi se poate observa formula (a+b)^2 )

La fel şi pentru următorul termen:

 \sqrt{4- 2\sqrt{3} } = \sqrt{1- 2\sqrt{3} + \sqrt{3}^2 } = \sqrt{(\sqrt{3}-1)^2} = \sqrt{3} -1

În final, avem:

 2- \sqrt{3} + \sqrt{3} -1 = 1, care \ este \ numar \ natural


1 5 1